DESIGNING LINE BALANCING FOR AMMUNITION BOX PRODUCTION USING HEURISTIC METHOD - Srijayasari, Hariti; Pratikto, Pratikto; Gapsari, Femiana (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2018)
PT XYZ is a State-Owned Enterprise that produces military equipment. Due to an increasing demand for such equipment every year, ammunition box sub-department asked their workers to work overtime and the total cycle time of ammunition box lid is higher than that of the ammunition box. Heuristic approaches, namely the Birnie Helgeson (RPW) and Moodie Young, are used to overcome these issues. This study aims to improve line balancing efficiency of ammunition box production. The findings showed that the Moodie Young method resulted in a 7.98% increase in line efficiency of the ammunition box lid and 21.77% increase in that of the ammunition box. In addition, the balance delay value decreased as much as the line efficiency. There are 9.09 and 152.87 decrease in the smoothing indexof the ammunition box lid and the ammunition box. The Moodie Young method cut the total labor cost to 9,597,170 rupiahs.